Professor Helena Harajda - Board, Editorial (Archives of Acoustics, 2011)
With deep sorrow we must let you know that Professor Helena Harajda passed away 25 April, 2011. As a close coworker of Professor Marek Kwiek she was actively involved in creating first Polish Centrum of Acoustics in Poznań (1950). Later on (1960), she was one of the founder of Polish Acoustical Society. During her professional activity she was employed in Adam Mickiewicz University, Musical Academy, Agricultural Academy in Poznań, also in Pedagogical High School in Zielona Góra (now University of Zielona Góra) and in Technical School for Violin Makers in Nowy Targ.The education of a violin-makers was her greatest passion. Her performancewas characterized by great engagement and dedication especially when she was teaching.Prof. Helena Harajda was always positive and forward-looking person. Therewill be many friends and colleagues who will miss her greatly.